The Development and Application of Cloud Storage Technology in Video Surveillance - Shan, Dedong (Journal of Theory and Practice of Engineering Science, 2024)
Cloud storage utilizes a cloud based data storage deployment model and distributed computing methods to aggregate a large number of different types of data storage devices in the network through application software, effectively and reasonably performing unified computing and data processing of resources and data. End users can access cloud storage data resources and business systems through remote or virtual access to desktop software applications and program interfaces, thereby achieving efficient and fast resource analysis and data processing in large-scale data storage and access environments. Therefore, this article provides a specific analysis of the development and application of cloud storage technology in video surveillance.